The Role of Foreign on Languages in the Human Resources Department in Recruitment of to do Hotel Employees at some Hotels in Dairi Regency - Mustafa Kamal (Politeknik Pariwisata Medan, 2021)
Mastery of foreign languages ​​is a mandatory imperative in the world of hospitality, especially hotels in urban areas with various tourist destinations. The Human Resources Department is obliged that foreign language is one of the requirements in recruiting hotel employees, Dairi Regency has quite a well-known tourist attraction and the number of hotels that can be said is sufficient, but whether hotel employees understand the role of foreign languages ​​is very necessary to deal with visitors from outside Indonesia, and What are the obstacles for HRD in recruiting employees that none of the candidates have foreign language skills. This research is a descriptive method in which the descriptive method is a research method that focuses on problems or phenomena that are actual at the time the research was carried out. Where is the conclusion of this study that there is still a lack of foreign language mastery of hotel employees in Dairi Regency, but business actors have made plans for the need for foreign languages ​​because there will be foreign parties from Wuhan who will invest in the tourism and hospitality sector in Dairi Regency.